(untitled) (Research, Society and Development, 2020)
This article is a temporal, quantitative and descriptive study of measles cases reported in Brazil, from 2013 to the first half of 2020, based on data available in epidemiological reports published on the Ministério da Saúde website. This study described the number of notifications registered in the period and analyzed the regions and states with the most cases of the disease. In the last 7 years, 38115 cases of measles were reported in Brazil, and approximately 96.6% were reported in 2018, 2019 and the first half of 2020. Although the North and South east regions have historically been more propitious for the spread of the disease, due to the high flow of migrants and tourists, it does not seem to be predictable the next state or city that will have a measles outbreak, since vaccination coverage rates may below throughout Brazil, influenced by anti-vaccine campaigns. Therefore, all Brazilian cities are susceptible to a measles outbreak, it is sufficient that the virus enters the population.